Long-Term Change Analysis of PM2.5 and Ozone Pollution in China’s Most Polluted Region during 2015–2020 - Yanpeng Li; Zhenchao Zhang; Yushan Xing (Atmosphere, 2022)
In this study, a time change analysis of fine particulate (PM2.5) emission in multi-resolution emission inventory in China (MEIC) from 2013 to 2016 was conducted. It was found that PM2.5 emissions showed a decreasing trend year by year, and that the annual total emission of PM2.5 decreased by 28.5% in 2016 compared with that of 2013. When comparing the observation data of PM2.5 and ozone (O3), it was found that both PM2.5 and O3 show obvious seasonal changes. The emission of PM2.5 in autumn and winter is higher than that in summer, while that of O3 is not. Our study showed that in the 2015–2020 period, annual mean concentrations of PM2.5 and O3 in Beijing varied from 80.87 to 38.31 μg m−3 and 110.75 to 106.18 μg m−3, respectively. Since 2015, the observed value of PM2.5 has shown an obvious downward trend. Compared with 2015, the average annual PM2.5 concentrations in Beijing, Shanghai, Xuzhou, Zhengzhou, and Hefei in 2020 had decreased by 52.62%, 40.35%, 22.2%, 46.84%, and 45.11%, respectively, while O3 showed an upward trend. Compared with the annual averages of 2015 and 2020, Beijing and Shanghai saw a decrease of 4.13% and 8.46%, respectively, while Xuzhou, Zhengzhou, and Hefei saw an increase of 7.08%, 19.46%, and 41.57%, respectively. The comparison shows that PM2.5 is becoming less threatening in China and that ozone is becoming more difficult to control. Air pollution is a modifiable risk factor. Appropriate sustainable control policies are recommended to protect public health.